Prevalence of Chronic Infection by Hepatitis C Virus in Asymptomatic Population With Risk Factors in Cartagena, Colombia - Imbeth-Acosta, Pedro; Leal-Martínez, Víctor; Ramos-Clason, Enrique; Pájaro-Galvis, Nehomar; Martínez-Ávila, María Cristina; Almanza-Hurtado, Amilkar; Rodríguez-Yanez, Tomás; Bermudez-Montero, Jorge; Vergara-Serpa, Oscar; Abuabara-Franco, Emilio; Raad-Sarabia, María; Villar-González, Erika Patricia; et al. (Frontiers in Medicine, 2022)
Introduction: Infection by the hepatitis C virus (HCV) is an important cause of chronic liver disease and only a small percentage of those affected know their infection status due to limited access to diagnostic tests, which is why a characterization of the population for the initiation of timely treatment. Objective: To determine the prevalence of chronic infection by hepatitis C virus in patients with risk factors by using rapid tests in Cartagena, Colombia and describe the epidemiological characteristics. Methodology: A cross-sectional descriptive observational study was carried out in asymptomatic adults with risk factors for HCV infection in the city of Cartagena between December 2017 and November 2019. A rapid immunochromatographic test was performed to detect antibodies, characterizing the population. Results: 1023 patients were identified who met the inclusion criteria, 58.5% women and 41.4% men, obtaining 9 positive results, confirming chronic infection with viral load for HCV, finding 7 cases genotype 1b and 2 genotype 1a. Conclusions: In our study, a prevalence of hepatitis C infection of 0.9% was found in asymptomatic individuals with risk factors, which allows us to deduce that the active search for cases in risk groups constitutes a pillar for the identification of the disease, the initiation of antiviral therapy and decreased morbidity and mortality.